ChemInform Abstract: Synthesis of 2‐Acyl‐1‐naphthols by Gold‐Catalyzed Oxidative Cyclization of 2‐Alkenylphenyl Alkynyl Ketones. Issue 22 (15th May 2015) - Matsuda, Takanori; Nishida, Yahiro; Yamanaka, Kentaro; Sakurai, Yusuke
Abstract: 2‐Acyl‐1‐naphthols [(II) and (IV)] as well as benzothiophenol (VI) and 10‐acyl‐9‐phenanthrenol (VIII), e.